Hippuric Acid Levels in Paint Workers at Steel Furniture Manufacturers in Thailand - Somsiri Decharat (Safety and Health at Work, 2014)
Background: The aims of this study were to determine hippuric acid levels in urine samples, airborne toluene levels, acute and chronic neurological symptoms, and to describe any correlation between urinary hippuric acid and airborne toluene. Methods: The hippuric acid concentration in the urine of 87 paint workers exposed to toluene at work (exposed group), and 87 nonexposed people (control group) was studied. Study participants were selected from similar factories in the same region. Urine samples were collected at the end of a shift and analyzed for hippuric acid by high performance liquid chromatography. Air samples for the estimation of toluene exposure were collected with diffusive personal samplers and the toluene quantified using gas–liquid chromatography. The two groups were also interviewed and observed about their work practices and health. Results: The median of the 87 airborne toluene levels was 55 ppm (range, 12–198 ppm). The median urinary hippuric acid level was 800 mg/g creatinine (range, 90–2547 mg/g creatinine). A statistically significant positive correlation was found between airborne toluene exposure and urine hippuric acid levels (r = 0.548, p < 0.01). Workers with acute symptoms had significantly higher hippuric acid levels than those who did not (p < 0.05). It was concluded that there was a significant correlation between toluene exposure, hippuric acid levels, and health (p < 0.001). Conclusion: There appears to be a significant correlation between workers exposure to toluene at work, their urine hippuric acid levels, and resulting symptoms of poor health. Improvements in working conditions and occupational health education are required at these workplaces. There was good correlation between urinary hippuric acid and airborne toluene levels.